Comparison Of Crestal Bone Loss Around Implants With Different Crown Materials - Kumar, P. Anil; Reddy B, Ravinder; Rajender, Koineni; Jawali Reddy, Muduganti; Soumya, K.; Reddy, T. Sudhakar (Journal of Neonatal Surgery, 2025)
Background: Crestal bone stability is a key indicator of long-term implant success. Different crown materials may influence biomechanical load transfer and thereby affect peri-implant bone remodeling. This study compared crestal bone loss (CBL) around implants restored with porcelain-fused-to-metal (PFM), monolithic zirconia, and resin-modified ceramic crowns. Materials and Methods: A prospective clinical study was conducted on 60 bone-level implants placed in 54 patients. Following standardized healing and prosthetic protocols, implants were randomly assigned to one of three crown material groups (n = 20 each). Crestal bone levels were measured radiographically at crown placement (baseline), 6 months, and 12 months using a standardized paralleling technique and digital analysis. Clinical parameters, including plaque index, probing depth, and bleeding on probing, were recorded. Results: All implants survived over the 12-month follow-up. Mean 12-month CBL was 0.68 ± 0.18 mm (PFM), 0.59 ± 0.15 mm (zirconia), and 0.64 ± 0.17 mm (resin-modified ceramic), with no statistically significant differences among groups (p > 0.05). Soft-tissue parameters remained stable and comparable across groups. Conclusion: Within the study limits, crown material did not significantly influence early crestal bone remodeling. All three restorative materials demonstrated minimal and clinically acceptable bone loss after 1 year of loading